2017
DOI: 10.1073/pnas.1714145115
|View full text |Cite
|
Sign up to set email alerts
|

Troy/TNFRSF19 marks epithelial progenitor cells during mouse kidney development that continue to contribute to turnover in adult kidney

Abstract: During kidney development, progressively committed progenitor cells give rise to the distinct segments of the nephron, the functional unit of the kidney. Similar segment-committed progenitor cells are thought to be involved in the homeostasis of adult kidney. However, markers for most segment-committed progenitor cells remain to be identified. Here, we evaluate as a segment-committed nephron progenitor cell marker. Troy is expressed in the ureteric bud during embryonic development. During postnatal nephrogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Results of PAS staining, showing loss and structural disturbance in brush borders, suggested that the proximal tubules were mainly impaired in the earlystage diabetic kidney. Molecular characterization of damaged renal tubules at the early stages of diabetes with the use of tubule segment-specific marker antibodies against megalin (a marker of the proximal tubule) and calbindin1 (a marker of the distal tubule) [30], revealed megalin antibody immunostaining in the proximal tubules ( Fig. 2a, b).…”
Section: Molecular Assessment Of Damaged Renal Tubules In Diabetic Kimentioning
confidence: 99%
“…Results of PAS staining, showing loss and structural disturbance in brush borders, suggested that the proximal tubules were mainly impaired in the earlystage diabetic kidney. Molecular characterization of damaged renal tubules at the early stages of diabetes with the use of tubule segment-specific marker antibodies against megalin (a marker of the proximal tubule) and calbindin1 (a marker of the distal tubule) [30], revealed megalin antibody immunostaining in the proximal tubules ( Fig. 2a, b).…”
Section: Molecular Assessment Of Damaged Renal Tubules In Diabetic Kimentioning
confidence: 99%
“…Concomitant with a proximal tubule transcriptional signature, FL clones demonstrated enhanced EMT, cell cycle and embryonic stem cell gene expression, suggestive of concomitant proliferative and de-differentiation states. Interestingly, the regenerative response to acute kidney injury is dependent on proximal tubular cells undergoing concurrent dedifferentiation and proliferation [7, 8]. Thus, transcriptional signature of FL clones mimics the regenerative response of proximal tubular cells to an acute kidney insult.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clonal proliferation is a mechanism of cell replacement in the adult kidney. Similarly, using lineage tracing in mice, LGR5+ cells were shown to mark distal tubular epithelial progenitors in development [6], while Schutgens et al showed that cells expressing the stem cell marker Tnfrsf19 (also known as Troy ), clonally contribute to tubular structures during development and continue to give rise to segment-specific collecting duct cells in homeostasis of the adult kidney [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been suggested that in humans, progenitor cells could preexist in the tubules, while, in rodents, dedifferentiation might predominate as the main regeneration mechanism [16]. However, this hypothesis was questioned by the detection of progenitor cells in rodent kidneys using other markers [38,50,64].…”
Section: State Of the Artmentioning
confidence: 99%
“…Papilla cells along with STCs in proximal tubules express progenitor cell markers, for instance, glycated CD133 in human kidneys or nestin in rodent kidneys, and these cells change their properties during tissue regeneration [30,61,62]. Furthermore, papilla cells are positive for embryonic kidney markers, for instance, Pax-2 [11] and TNFRSF19 [64], even in intact adult kidneys.…”
Section: Renal Papilla As a Niche For Progenitor Cellsmentioning
confidence: 99%